A CASE OF GRAVE FLU A(H1N1) WITH PNEUMONIA AND ACUTE RESPIRATORY DISTRESS-SYNDROME IN THE BABY - N. V. Minaeva; E. G. Furman; T. K. Rysinskaya; A. R. Bakyrova; A. G. Lebedev; N. A. Ososova; L. A. Velixar; T. A. Sozykina (Медицинский совет, 2017)
The article considers a clinical case of the grave course of the flu А(Н1N1)pdm09 with development of the viral and bacterial pneumonia and acute respiratory distress-syndrome (ARDS) in the baby. A description of the respiratory support is provided, the data on catamnesis in a year are given.